PENGARUH LAMA PENGERINGAN TERHADAP KUALITAS KIMIA DAN BIOLOGIS IKAN TERI ASIN KERING (Stolephorus sp.)PENGARUH LAMA PENGERINGAN TERHADAP KUALITAS KIMIA DAN BIOLOGIS IKAN TERI ASIN KERING (Stolephorus sp.) - Bau, Fikri Cahyanto; Une, Suryani; Antuli, Zainudin (Universitas Negeri Gorontalo, 2023)
ABSTRACT Anchovies like sea fish, are generall, an important source of nutrition for Indonesian people. Anchovies commonly contains protein about 16% and only 1% fat content. Water is the most component in anchovies meat, namely 80% so that anchovies will be easily damaged. The research aimed to find out the chemical and biological quality of dried-salted anchovies (Stolephorus sp.). It applied a Randomized Block Design (RBD) with a single factor, namely the effect of drying time for 4 hours, 8 hours, 12 hours, and 24 hours where each treatment was replicated three times. The parameter observed in this research included chemical quality (proximate test) and microbiological quality). In addition, the data analysis used was Analysis of Variance (ANOVA). The result of water content quality on driedsalted anchoves revealed the value for 22.34 18.76%; for protein analysis showed a value of protein content was 31. 89 -33. 15%; for fat analysis, the percentage value of fat content was 1.61 2. 84%. Meanwhile, for the analysis of total plate count (TPC) showed a significant value was 22. 2 cfu/g for 4 hours dryng 21 2 CfU/g for 8 hours drying, and 14. 2 cfu/gr for 12 hours dryng.